Lipiodol flush under ultrasound guidance in Australia. (9th September 2020) - Sekhon, Jasmin; Lee, Emmeline; Lo, Glen; Woolcock, Jane; Ramkrishnan, Jayshree; Menezes, Melody; Tan, Shawn; Meagher, Simon; Murphy, Anthony
Abstract : Background: Lipiodol tubal flushing is offered to select subfertile women primarily to confirm tubal patency and to increase pregnancy rates. Aims: To investigate the safety of hystero‐salpingo contrast sonography (HyCoSy) using Lipiodol flush (through frequency of adverse events and mean recalled pain score) and secondarily to quantify pregnancy rates. Materials and Methods: Retrospective observational Phase 1 study of subfertile women in three centres across Australia between June 2017 and June 2019. Cases were identified from medical records, and women telephoned to assess adverse outcomes, procedure tolerability and confirm pregnancy outcomes within six months from procedure. Results: A total of 325 cases were identified; 14 were excluded due to incomplete or abandoned procedure, 32 were lost to follow‐up, leaving 279 for analysis. Fourteen women (5% overall) experienced mild vasovagal reactions, with one case of infection and no reports of anaphylaxis or allergy. There were 141 conceptions reported (51%) within six months after Lipiodol flush, and an ongoing pregnancy in 43% (119) of women. For women with ongoing pregnancies, 55% (78/119) conceived spontaneously, and 45% (63/119) via artificial reproductive technology. Mean recalled pain score was 5.7 (SD 3.2; range 0‐10) at a single site. Conclusions: This Phase 1 study has indicated that Lipiodol flush using HyCoSy may be a safe and efficacious alternative to hysterosalpingography in the workup for infertility. The low adverse effect profile observed in this study coupled with a substantial ongoing pregnancy rate indicates that further investigation of Lipiodol under HyCoSy is warranted.